2016
DOI: 10.1002/pmic.201600151
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune response to lipoproteins of Staphylococcus aureus in healthy subjects

Abstract: Staphylococcus aureus is a frequent commensal but also a dangerous pathogen, causing many forms of infection ranging from mild to life‐threatening conditions. Among its virulence factors are lipoproteins, which are anchored in the bacterial cell membrane. Lipoproteins perform various functions in colonization, immune evasion, and immunomodulation. These proteins are potent activators of innate immune receptors termed Toll‐like receptors 2 and 6. This study addressed the specific B‐cell and T‐cell responses dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Notably, the response was superior to that elicited by the MRSA-specific PBP2a or the lipoprotein SitC, which confirms a previous report [43]. This might be due to the fact that SpA is expressed in high quantity on the cell wall of 99% of S .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, the response was superior to that elicited by the MRSA-specific PBP2a or the lipoprotein SitC, which confirms a previous report [43]. This might be due to the fact that SpA is expressed in high quantity on the cell wall of 99% of S .…”
Section: Discussionsupporting
confidence: 88%
“…The short time frame avoids in vitro amplification, an important confounder in classical assays such as chromium release assay and limiting dilution assays that require T cell expansion to increase sensitivity [40,41]. Notably, these methodological differences may account for differences in the quantitative and qualitative outcome of T cell responses to other studies that observed higher frequencies of antigen-specific T cells or predominant Th1 responses [16,43,15,44]. …”
Section: Discussionmentioning
confidence: 99%
“…In serological proteome analysis (SERPA), a major problem is alignment of 2D protein spots with the antigen pattern immunopositive after probing the membrane with patient serum [46]. Identification of bacterial antigens or autoantigens was often complicated due to different complexity levels in protein and immunopositive pattern or high antigenicity despite low protein abundance, interfering with post-experimental alignment [91,92,93]. In order to circumvent this, other attempts include the application of internal markers [94], additional staining steps [91], and alternative usage of protein arrays [95,96] or Luminex assays [97] based on recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus has emerged as an important human pathogen and is the causative agent of several nosocomial infections (1). It overcomes not only the challenging stress and starvation conditions of the ever-changing environment of bacterial habitats, but also host defense mechanisms and antibiotic treatments (2,3). Furthermore, Staphylococcus aureus (S. aureus) 1 can express a high number of different virulence factor proteins that boost pathogenicity by complex mechanisms (4).…”
mentioning
confidence: 99%
“…Because of their negative charge, phosphorylations can induce conformational changes to enable effects on protein structure, protein-protein interactions, protein activity or changes in substrate specificity and subcellular localization (6 -8). To date, phosphorylation events on four different groups of amino acid residues are known: (1) the phosphorylation on hydroxyl groups to form phosphoesters (9,10), (2) the phosphorylation on acidic groups to form phosphoanhydrides (11), (3) the phosphorylation on cysteine moieties to form thioesters (12), and (4) the phosphorylation on amide groups to form phosphoamidates (13,14).…”
mentioning
confidence: 99%